The Development of Non-bank Financial Institutions in Ukraine : Policy Reform Strategy and Action Plan - Noel, Michel; Kantur, Zeynep; Prigozhina, Angela; Rutledge, Sue; Fursova, Olena (Washington, DC: World Bank, 2012)
The prospect of European integration presents huge opportunities and challenges for the development of non-bank financial institutions (NBFIs) in Ukraine. By most measures, the development of the NBFI sector in Ukraine lags far behind that of recent accession countries in Central Europe. To address the main impediments facing the development of the sector, the Ukrainian authorities need to implement a strategy based on six main pillars: 1) strengthen the capacity, independence, funding, and accountability of the NBFI regulators; 2) develop money markets, government bond markets, and municipal bond markets; 3) restructure equity markets; 4) accelerate the introduction of funded pension schemes, and, improve transparency and consumer protection in the insurance industry; 5) radically transform corporate governance; and, 6) broaden access of NBFI finance.